Le rapport à l'élève idéal d'enseignants du premier degré : quelles répercussions sur la scolarisation des élèves à besoins éducatifs particuliers ? - Déborah Saunier (Nantes Université, 2021)
By laying the foundations of the inclusive school, the law of 8th July 2013, on the refoundation of the school, has changed the daily life of teachers. Although overwhelmingly in favour of the schooling of pupils with special educational needs, they express reservations and ambivalence which can be explained in particular by « the weight of traditional pedagogical models which postulate that pupils conform to an ideal, successful and... in good health pupil model! » Using data from a quantitative survey and focus groups interviews, this research questions the influence of representations of the ideal pupil on the professional practices and identity of primary school teachers in the context of inclusive schooling. Our results have enabled us to draw a portrait of the ideal pupil and to highlight contradictions between some of his or her characteristics and some profiles of pupils with special educational needs.